Dose-dependent effect of statins on the change in the content of individual fatty acids of blood serum and their complexes of men and women with secondary prevention of chronic coronary heart disease - M. Yu. Kotlovsky; A. M. Dygai; O. Yu. Trifonova; V. V. Zhdanov; V. V. Udut; A. A. Churin; I. Yu. Yakimovich; V. N. Titov; E. V. Krasnov; L. Yu. Kotlovskya (Бюллетень сибирской медицины, 2018)
Objective. To study the dose-dependent effect of simvastatin on the change of content of individual fatty acids (FA) profile of blood serum and their complexes with secondary prevention of chronic coronary heart disease (CHD) in groups of men and women.Materials and methods. Gas-liquid chromatography-mass spectrometry was used to establish the absolute and relative levels of FA in serum of 155 CHD patients before and after treatment by simvastatin in doses of 40 mg (89 people) and 80 mg (36 people).Results. The statin lowered the content of the FA proportionally by reducing the unsaturated (UFA), mainly polyunsaturated (PUFA) FA, and saturated (SFA) FA. The level of monounsaturated fatty acids (MUFA) decreased in women at a dose of 40 mg. The statin increased endogenous formation of ω6 PUFA, ω9 MUFA, and SFA even (except 80 mg), in group of women (40 mg) – ω3 PUFA, and in men (80 mg) – ω7 MUFA. In women after receiving simvastatin 80 mg, the ratio ω3/ω6 PUFA has been shifted to ω6 PUFA, but in men after receiving simvastatin 40 mg in the direction of ω3 PUFA. Only the dose of 80 mg shifted the ratio of C20:5/C20:4 in the direction of ω3 PUFA. In group of women after receiving simvastatin 40 mg was observed a shift to β-oxidation of C18:1(9), and in men at the dose of 80 mg in the direction of its synthesis. In all cases, increased antioxidant protection of PUFA, but less strong it was at the dose of 40 mg. At the same time the formation of MUFA prevailed over the synthesis of SFA. Absolute content of FA - substrates of energy decreased. In all cases, was noticed the decrease of content of FA this very long chain (C22-26), stronger in women.Conclusion. Simvastatin controlling the quantitative composition of the pool of circulating lipoproteins, FA and cholesterol, is ambiguous, depending on dose, affect the metabolism of fatty acids, changing their quantitative and qualitative composition and performing biological functions.